2018
DOI: 10.1085/jgp.201812005
|View full text |Cite
|
Sign up to set email alerts
|

Duplex signaling by CaM and Stac3 enhances CaV1.1 function and provides insights into congenital myopathy

Abstract: Ca1.1 is essential for skeletal muscle excitation-contraction coupling. Its functional expression is tuned by numerous regulatory proteins, yet underlying modulatory mechanisms remain ambiguous as Ca1.1 fails to function in heterologous systems. In this study, by dissecting channel trafficking versus gating, we evaluated the requirements for functional Ca1.1 in heterologous systems. Although coexpression of the auxiliary β subunit is sufficient for surface-membrane localization, this baseline trafficking is we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 103 publications
(175 reference statements)
2
10
0
Order By: Relevance
“…Stac regulation of Ca V 1 modifies multiple aspects of Ca V 1 function. For Ca V 1.1, stac3 enhances plasmalemmal trafficking ( Linsley et al, 2017b ; Niu et al, 2018 ; Polster et al, 2015 ; Wong King Yuen et al, 2017 ; Wu et al, 2018 ), and promotes conformational coupling to RyR ( Linsley et al, 2017a ; Polster et al, 2016 ). For Ca V 1.2, however, stac1-3 isoforms slow inactivation ( Campiglio et al, 2018 ; Polster et al, 2015 ; Wong King Yuen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stac regulation of Ca V 1 modifies multiple aspects of Ca V 1 function. For Ca V 1.1, stac3 enhances plasmalemmal trafficking ( Linsley et al, 2017b ; Niu et al, 2018 ; Polster et al, 2015 ; Wong King Yuen et al, 2017 ; Wu et al, 2018 ), and promotes conformational coupling to RyR ( Linsley et al, 2017a ; Polster et al, 2016 ). For Ca V 1.2, however, stac1-3 isoforms slow inactivation ( Campiglio et al, 2018 ; Polster et al, 2015 ; Wong King Yuen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A few mechanistic nuances merit attention. First, stac binds to multiple Ca V 1 segments including (1) the II-III linker ( Polster et al, 2018 ; Wong King Yuen et al, 2017 ), (2) the III-IV linker ( Figure 2D ), and (3) the carboxy-tail ( Figure 2D ) ( Campiglio et al, 2018 ; Niu et al, 2018 ). Previous studies have shown that stac interaction with the II-III linker is important for Ca V 1 trafficking in skeletal muscle ( Polster et al, 2018 ; Wong King Yuen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several years ago, Polster et al (2015) demonstrated that STAC3 facilitates expression and membrane targeting of Ca V 1.1 in tsA201 cells, and later, this function of STAC3 was shown to be due to the interaction of the PKC C1 domain of STAC3 with the C-terminal domain of the DHPR-α 1s (Campiglio et al 2018a;Campiglio and Flucher 2017). This interaction was also shown to play a role in the inhibition of calcium-dependent inactivation of Ca V channels (Campiglio et al 2018a;Niu et al 2018a;Niu et al 2018b); however, it does not appear to be directly relevant to the ECC. In a followup work, Polster et al (2016) showed that the STAC3 is not absolutely required for membrane targeting of Ca V 1.1 in tsA201 cells, as this role could also be accomplished by the γ-subunit of DHPR; however, STAC3-null myotubes with properly membrane-targeted Ca V 1.1 did not have functional ECC, thus implicating the direct role of STAC3 in mediating the interactions between DHPR and RyR1 (Polster et al 2016).…”
Section: Stac3mentioning
confidence: 99%
“…One unique property of Ca v 1.1 among Ca V s is that it does not express well in nonmuscle cells ( 62 , 63 , 64 ). Although coexpression of Ca v 1.1 with the β and α 2 δ subunits gives low baseline membrane expression, this complex is mostly retained in the endoplasmic reticulum of heterologous systems ( 48 , 65 ), and this has hampered systematic functional investigation of Ca V 1.1 via heterologous expression. However, when coexpressed also with STAC3, Ca v 1.1 robustly traffics to the plasma membrane ( 60 ).…”
Section: Functional Effects Of Stacs On Ca V Channelsmentioning
confidence: 99%